National trends of hepatocellular carcinoma mortality registered by the ministry of health in Peru, from 2005 to 2016 - Piscoya, Alejandro (2020)
Background. Hepatocellular carcinoma results in most cases from underlying chronic liver disease. The most common causes are the Hepatitis B virus and the Hepatitis C virus in-fections, the alcoholism and the aflatoxin. Mortality statistics of liver cell carcinoma in Peru is limited. Objectives. Update statistics on hepatocellular carcinoma mortality in Peru between the years 2005 and 2016. Methods. Observation-al, descriptive studyand secondary analysis of the Ministry of Health database. Records with the basic cause of death ICD 10: C22, the liver cell carcinoma were reviewed. Mortality was calculated according to the age, the sex and the department in which death was recorded; Also, standardized mortality by age was calculated. Results. 2,170 people were registered as deceased due to hepatocellular carcinoma. The 50.1% were male and the 67.5% older than 60 years. The standardized mortality rate in Peru decreased from 1.1 to 0.7 per 100,000 population from 2005 to 2016. The raw cup of mortality per 100,000 population shows that when comparing the first period (2005-2010) with the second (2011-2016), the tendency in Peru has decreased. The only region that presented a decrease in mortality was the Mountains (% change =-40.1). Conclusions. Standardized mortality by age had a slight decrease from 2005 to 2016; however, this difference does not show considerable variations. Mortality from this neoplasm seems to remain high and stable since the period from 1995 to 2000.